The Ritual and Religious World of Coporaque: Apus, Saints, and the Cult of the Dead in a Peasant Community of the Southern Andes of Peru - Aleixandre Brian Duche-Pérez; Gonzalo Ríos-Vizcarra; Luis Enrique Calatayud-Rosado (Zeszyty Wiejskie)
This ethnographic study explores the rich tapestry of ritual and cultural practices in Coporaque, a peasant community in the southern Andes of Peru, highlighting the deep integration of religiosity into everyday life. Coporaque, with roots dating back to pre-Incan times, reflects a unique synergy of pre-Columbian and Catholic influences that manifest through rituals and festivities ranging from the celebration of the Day of the Dead to the festivities of San Santiago and the Cocha fiesta. The study employs an ethnographic approach consisting of participant observation and semi-structured interviews, facilitating an understanding of how faith and the veneration of natural elements, such as the Apus and cochas, contribute to community cohesion and cultural continuity. The findings highlight how the community strives to maintain its ancestral traditions while facing the challenges of modernity and emphasize the role of these practices in fostering a sense of community identity and cultural resilience.